Two-way NxP fertilisation experiment on barley (Hordeum vulgare) reveals shift from additive to synergistic N-P interactions at critical phosphorus fertilisation level - Clayton, Jessica; Lemanski, Kathleen; Solbach, Marcel Dominik; Temperton, Vicky M.; Bonkowski, Michael (Frontiers in Plant Science, 2024)
In a pot experiment, we investigated synergistic interaction of N and P fertilisation on barley biomass (Hordeum vulgare) on both shoot and root level with the aim to determine whether N-P interaction would be the same for all levels of N and P fertilisation. We further aimed to determine whether there was a critical level of N and/or P fertilisation rate, above which, a decrease in resource allocation to roots (as nutrient availability increased) could be demonstrated. Barley plants were grown from seed on a nutrient poor substrate and subjected to a two-way NxP fertilisation gradient using a modified Hoagland fertilisation solution. We observed N-P interactions in shoot and root biomass, and N and P use-efficiencies. A synergistic response in biomass was observed only above a critical level of P fertilisation when P was not limiting growth. Furthermore, we found that the same incremental increase in N:P ratio of applied fertiliser elicited different responses in shoot and root biomass depending on P treatment and concluded that barley plants were less able to cope with increasing stoichiometric imbalance when P was deficient. We provide, for the first time, stoichiometric evidence that critical levels for synergistic interactions between N-P may exist in crop plants.